Penggunaan Komposit Karbon Aktif Termodifikasi Kitosan/Alginat Beads sebagai Adsorben Rhodamin B - Anne, Chintya; Setyaningtyas, Tien; Riyani, Kapti (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2025)
Activated carbon is one of the adsorbents that has a large surface, high porosity, and various functional groups on its surface. However, synthesized activated carbon is generally a powder that is difficult to separate from water, so it has low reuse effectiveness. Therefore, it is necessary to modify it to increase its adsorption effectiveness and also increase its adsorption capacity. One of them uses chitosan and activated carbon into beads, as shown in previous studies that reported high adsorption capacity of methylene blue (MB) dye. This modification is relevant to handle the problem of industrial wastewater containing hazardous dyes, such as rhodamine B, which has high stability and is difficult to biodegrade. This study aims to analyze the adsorption process of rhodamine B using KAKatea composite beads focusing on the optimum conditions, isotherm model, and reuse effectiveness. The results showed that the optimum conditions of adsorption were at a contact time of 210 minutes and rhodamine B pH of 3. This adsorption process followed the Freundlich isotherm model with reuse effectiveness reaching 82% for five cycles.